Site-selective tagging of proteins by pnictogen-mediated self-assembly. Issue 79 (11th September 2017) - Nitsche, Christoph; Mahawaththa, Mithun C.; Becker, Walter; Huber, Thomas; Otting, Gottfried
Abstract : Trivalent pnictogens (Pn) enable the selective self-assembly between an engineered di-cysteine motif in a protein and a thiol-containing lanthanide (Ln) probe. Abstract : Site-selective chemical protein modification is achieved by self-assembly of a specific di-cysteine motif, trivalent pnictogens (As, Sb or Bi) and an aromatic mercaptomethyl-based probe. The strategy is demonstrated with a quaternary complex involving Zika virus protease and a lanthanide ion, enabling paramagnetic nuclear magnetic resonance spectroscopy and luminescence measurements.